Hearing evaluation of patients with head and neck cancer: Comparison of Common Terminology Criteria for Adverse Events, Brock and Chang adverse event criteria in patients receiving cisplatin. Issue 8 (11th July 2014) - Colevas, A. Dimitrios; Lira, Ruth R.; Colevas, Electra A.; Lavori, Philip W.; Chan, Cato; Shultz, David B.; Chang, Kay W.
Abstract Background The purpose of this study was to compare Common Terminology Criteria for Adverse Events (CTCAE), Brock and Chang hearing loss grading in patients with head and neck cancer receiving cis‐diamminedichloroplatinum (CDDP). Endpoints were baseline distribution of hearing loss, interobserver consistency, and sensitivity to hearing loss after CDDP treatment. Methods Four hundred sixty single ear audiograms in 110 patients with head and neck cancer were graded. Hearing loss at baseline, interobserver agreement rates, and changes in hearing loss after CDDP were evaluated. Results The Chang and Brock tools' baseline hearing loss distribution was concentrated at grade 0 (57% and 41%, respectively), whereas 47%, per the CTCAE, had grade 3 baseline hearing loss. Interobserver agreement was highest for the Brock scale (≥90%) followed by the Chang (≥89%) and CTCAE (≥75%) scales. Detection of change after CDDP was highest for Chang (48%) followed by Brock (45%) and the CTCAE (32%). Conclusion The Brock and Chang tools may be superior to the CTCAE in patients with head and neck cancer receiving CDDP using baseline hearing loss distribution, interobserver agreement, and detection of hearing loss grade change as performance indicators. © 2014 Wiley Periodicals, Inc. Head Neck37: 1102–1107, 2015